Evaluating plant growth–defense trade-offs by modeling the interaction between primary and secondary metabolism - Jan Zrimec; Sandra Correa; Maja Zagorščak; Marko Petek; Carissa Bleker; Katja Stare; Christian Schuy; Sophia Sonnewald; Kristina Gruden; Zoran Nikoloski (Proceedings of the National Academy of Sciences, 2025)
Understanding the molecular mechanisms behind plant response to stress can enhance breeding strategies and help us design crop varieties with improved stress tolerance, yield, and quality. To investigate resource redistribution from growth- to defense-related processes in an essential tuber crop, potato, here we generate a large-scale compartmentalized genome-scale metabolic model (GEM), potato-GEM. Apart from a large-scale reconstruction of primary metabolism, the model includes the full known potato secondary metabolism, spanning over 566 reactions that facilitate the biosynthesis of 182 distinct potato secondary metabolites. Constraint-based modeling identifies that the activation of the largest amount of secondary (defense) pathways occurs at a decrease of the relative growth rate of potato leaf, due to the costs incurred by defense. We then obtain transcriptomics data from experiments exposing potato leaves to two biotic stress scenarios, a herbivore and a viral pathogen, and apply them as constraints to produce condition-specific models. We show that these models recapitulate experimentally observed decreases in relative growth rates under treatment as well as changes in metabolite levels between treatments, enabling us to pinpoint the metabolic rewiring underlying growth–defense trade-offs. Potato-GEM thus presents a useful resource to study and broaden our understanding of potato and general plant defense responses under stress conditions.